Determinan Akuntabilitas Pengelolaan Dana Desa: Studi Kasus Pada Pemerintahan Desa Se-Kecamatan Ubud - Ni Kadek Suardiani; I Wayan Sudiana; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2026)
Based on the issues being studied, this research uses a quantitative approach. The sample taken consists of the Village Head, Village Secretary, Financial Officer, General Officer, Planning Officer, and Village Consultative Body (BPD), resulting in a total sample of 42 respondents. The conclusions of this study can be summarized as follows: 1) The implementation of the village financial system has a positive and significant impact on the accountability of village funds (Case study on villages in Ubud District, Bali). 2) Internal controls have a positive and significant effect on the accountability of village funds (Case study on villages in Ubud District, Bali). 3) The Adjusted R-Square value of 0.631 indicates that 63.1% of the independent variable is explained by the dependent variable, while the remaining 36.9% is explained by other variables or factors.